Coaches` perspective towards skill acquisition in swimming: What practice approaches are typically applied in training? - Brackley, V.; Barris, S.; Tor, E.; Farrow, D. (Journal of Sports Sciences, 2020)
This study aimed to explore the experiential knowledge and preferred training approaches of elite swimming coaches in regards to general skill development and then looking specifically at the freestyle stroke. A qualitative thematic analysis approach was employed to identify, analyse and report themes within the content of the collected data. Twenty elite swimming coaches participated in semi-structured interviews. Several themes revealed that the most common training practices employed to improve skill learning included the use of task decomposition (part-task) techniques. The findings also indicated that swimming coaches believe practice should be specific/representative to the intended performance outcomes. It is believed that such viewpoints may have been influenced by coaches` interaction with skill acquisition consultants and may have also shaped some coaches use of variants of constraints manipulation in their practice design. While swimming coaches seem to mix both traditional and contemporary skill acquisition theories in their training prescriptions, the traditional approach is dominant as evidenced by coaches seeking to reinforce "perfect" swimming technique and mechanical consistency. Considering coaches` experiential knowledge and training prescriptions may benefit future research protocols and better facilitate the transfer of empirical findings to coaching practice.